Islamic Education Policy on Socio Political System - Ahmad Wahyu Hidayat; Muhamad Iqbal Fasa (AT-TURATS, 2020)
Islamic education is often known as Islamic education. Islamic education is recognized for its existence in Indonesia, seen from Islamic education institutions that are established and developing today. On the other hand, Islamic education is recognized for its existence as seen from various government policies on religious subjects taught in schools. Socio Political System was the time of the replacement of President Soekarno's administration to President Soeharto's administration in 1966 until 1998. The Islamic education policy in the early days of Socio Political System was the integration of madrassas in the Old Order. In addition, the establishment of Islamic educational institutions both formal and non-formal. In schools, religious subjects become compulsory subjects that must be taught in both religious schools, public schools, private and public schools. The focus of this research was on the development of Islamic education and the Islamic education policy of Socio Political System. This study uses a qualitative approach with analytical study methods. The analytical study used is analytical historical and analytical policy. Islamic education during Socio Political System stage by step experienced a development among which pesantren institutions began to establish madrassas in their education systems. In this system the levels of education are divided into Ibtidaiyah, Tsanawiyah and Aliyah. The government applies a policy that religious education must be taught starting from elementary school (SD) to university. Islamic education is growing with the emergence of several institutions and programs of Islamic religious teaching activities.